Mid-Term Outcome of Total Knee Replacement with All-Poly Ethylene Tibial Components (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the mid-term functional and radiographic outcome of primary total knee replacement with all-polyethylene tibial components.Methods: This descriptive study was conducted in Orthopaedic Department of Ghurki trust Teaching Hospital Lahore from 25th June 2014 to 29th June 2019.All patients fulfilling the inclusion criteria who were operated with all-polyethylene tibial component were included in our study. Post-operative functional outcome was assessed at three years with Knee Society Score and graded as excellent, good, fair and poor for Knee score and Function. Radiological outcome was assessed by measuring tibial angle, tibial-femoral angle and femoral flexion angle on anterio posterior and lateral radiographs.Results: During this study 65 knees of 34 patients were replaced by using all-polyethylene tibial component implant. Male patients were 15(44.1%) and females 19 (55.8%). Mean age of our patients were 60.4±6.12 years (range 50-80 years). Bilateral total knee replacement (TKR) was done in 31(91.1%) patients while 3(8.8%) had unilateral knee Arthroplasty. At three years follow up the knee score was excellent in 3(8.8%), good in 15(44.1%), fair in 12(35.2%) and poor in 4(11.7%) patients. The function score was good in 11(32.3%) fair in 14(41.1%) and poor in 9(26.4%). Anterio posterior radiograph revealed mean tibial angle 89±1.72°(range 84-92°), tibia-femoral angle 5.0±0.53°(range 4-6°) and femoral flexion angle 96±1.88°( range 94° to 102°).Lateral radiograph showed mean tibial angle 89.9±1.24°(range 85 to 92°) and mean femoral flexion angle 10.83±1.49°(range 10-16°).Conclusion: Total knee replacement with all- polyethylene tibial components had excellent and good functional and radiological mid-term outcome in majority of our patients